Microsomal triglyceride transfer protein inhibitor (lomitapide) efficacy in the treatment of patients with homozygous familial hypercholesterolaemia. (January 2020) - Kolovou, Genovefa; Diakoumakou, Olga; Kolovou, Vana; Fountas, Epameinondas; Stratakis, Stavros; Zacharis, Evangelos; Liberopoulos, Evangelos N; Matsouka, Fedra; Tsoutsinos, Alexandros; Mastorakou, Irene; Katsikas, Theodoros; Mavrogeni, Sophie; et al.
Aims: The aim of this study was to evaluate the effect of microsomal triglyceride transfer protein inhibitor (lomitapide) in patients with homozygous familial hypercholesterolaemia. Methods and results: In 12 homozygous familial hypercholesterolaemia patients treated with lipid-lowering drugs ± biweekly lipoprotein apheresis sessions (nine patients), daily lomitapide was added. The lipid profile (total cholesterol, low-density lipoprotein cholesterol, triglycerides, high-density lipoprotein cholesterol) before and after lomitapide treatment was evaluated. The follow-up period with lomitapide treatment was 3–24 months (13.8 ± 7.9). The median baseline low-density lipoprotein cholesterol level was 900 mg/dl (348–1070), after lipid-lowering drugs therapy was 383.5 mg/dl (214–866) and after lipid-lowering drugs + time-averaged level was 288 mg/dl (183.7–716.6). The addition of lomitapide lowered low-density lipoprotein cholesterol levels further by 56.8% compared to lipid-lowering drugs alone (mean reduction 262, 95% confidence interval (105.5–418.7), p = 0.005) and by 54% (mean reduction 182.9, 95% confidence interval (−342 – −23), p = 0.031) comparing to lipid-lowering drugs + lipoprotein apheresis (time-averaged level). The time-averaged level of low-density lipoprotein cholesterol in lipid-lowering drugs + lipoprotein apheresis patients compared with lipid-lowering drugs + lomitapide was 54% in favour of lomitapide ( p = 0.031). Conclusions: Treatment with lomitapide in homozygous familial hypercholesterolaemia patients has a beneficial effect with a constant decrease of low-density lipoprotein cholesterol by 57% compared with classical lipid-lowering therapy and by 54% compared with classical lipid-lowering therapy and time-averaged level of low-density lipoprotein cholesterol.